Compressing the Channels in the Crystal Structure of Copper Squarate Metal-Organic Framework - Francisco Colmenero; Álvaro Lobato; Vicente Timón (Solids, 2022)
The crystal structure of a copper squarate metal-organic framework is fully determined using first principles methods based in density functional theory. The compressibility of this material is studied by optimizing the structure under different isotropic pressures and uniaxial stresses directed along the direction of minimum compressibility, [1 0 0]. Under isotropic compression, channels become wider along [1 0 0], leading to negative linear compressibility, NLC. Under compression along [1 0 0], the unit-cell volume increases leading to negative volumetric compressibility.